2022
DOI: 10.3389/fneur.2022.1019671
|View full text |Cite
|
Sign up to set email alerts
|

Venous stroke–a stroke subtype that should not be ignored

Abstract: Based on the etiology, stroke can be classified into ischemic or hemorrhagic subtypes, which ranks second among the leading causes of death. Stroke is caused not only by arterial thrombosis but also by cerebral venous thrombosis. Arterial stroke is currently the main subtype of stroke, and research on this type has gradually improved. Venous thrombosis, the particular type, accounts for 0.5–1% of all strokes. Due to the lack of a full understanding of venous thrombosis, as well as its diverse clinical manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 183 publications
(198 reference statements)
0
8
0
Order By: Relevance
“…Cerebrovascular homeostasis depends on continuous blood perfusion to deliver oxygen and glucose in order to maintain a normal brain metabolic state [ 28 , 29 ]. Because 70% of the cerebral blood volume is located in the veins, the regulation of the cerebral venous system is as vital as that of the cerebral artery system [ 1 , 3 , 30 , 31 ]. During natural cerebral circulation, cerebral autoregulation prevents and protects the brain from overflow-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrovascular homeostasis depends on continuous blood perfusion to deliver oxygen and glucose in order to maintain a normal brain metabolic state [ 28 , 29 ]. Because 70% of the cerebral blood volume is located in the veins, the regulation of the cerebral venous system is as vital as that of the cerebral artery system [ 1 , 3 , 30 , 31 ]. During natural cerebral circulation, cerebral autoregulation prevents and protects the brain from overflow-induced injury.…”
Section: Discussionmentioning
confidence: 99%
“…Among the etiological causes associated with CVST, various previous studies have considered and identified general well‐known risk factors (Dentali et al, 2006; Silvis et al, 2018; Zhou et al, 2022). Other hypothetical structural causes have received less attention; nevertheless, since CVST is a multifactorial disorder with a high frequency of cases of unknown etiology, comprehensive consideration of factors concerning the angulation such as those measured in the present study are relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that this entity accounts for 0.5%-1% of all strokes. However, the past incidence of CVST could have been noticeably underestimated compared with current cases, mainly owing to an opportunistic approach to this condition in an emergency setting, its association with the recent pandemic, and its development after SARS-CoV-2 vaccination (Ferro et al, 2021;Jianu et al, 2018;Zhou et al, 2022Zhou et al, , 2023.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral stroke includes ischemic stroke and hemorrhagic stroke, and leads to large amount of death with high incidence and teratogenic rate ( Grysiewicz, Thomas & Pandey, 2008 ). On the occurrence of cerebral stroke, especially ischemic stroke, cerebrovascular thrombosis serves as a vital factor ( Ding et al, 2022 ; Hu et al, 2022a ; Zhou et al, 2022 ). So far, NETs have been widely reported to be important in the pathological process of cerebral stoke, and the role of NETs in stroke is most studied among all kinds of CNS diseases.…”
Section: Part Ii: Nets In Cns Diseasesmentioning
confidence: 99%